PHYSIOTHERAPY INTERVENTION IN VESTIBULAR MIGRAINE: AN EXPERIMENTAL STUDY - Shahanawaz, S D; Henali, Parikh (International Journal of Ayurveda and Pharma Research, 2015)
Background: The prevalence of migraine, according to the criteria of the International Headache Society (IHS), is at least three times higher in those with vertigo. Patients with various forms of disequilibrium and some manifestations of migraine may have a condition known as vestibular migraine (VM), also known as migraine-associated vertigo or migrainous vertigo, migraine related Vestibulopathy, have all been applied to roughly the same patient population. Migraine is a very common, chronic neurological disorder, affecting about 6 % of men and 15 % to 18 % of women with the highest prevalence between the ages of 25 and 55. The public health burden of migraine is high because migraine attacks are associated with temporary disability and substantial impairment in activities. Headache experts have proposed that regular, moderate aerobic exercise improves cardiovascular fitness and helps to reduce the frequency, severity and duration of migraine attacks in with or without aura. Whitney suggested that vestibular exercise is beneficial for migraine, but it reduce the vestibular symptoms in migraine.Method: Randomized Controlled Sample of 30 subjects with vestibular migraine was taken for the study. The subjects were divided into two groups. Outcome measured HIT, DHI were taken pre and post treatment. Group A is experimental group and Group B is control Group. Group A received design protocol for thirty days, five days a week till six weeks, each day one session. Group B received shoulder and neck ROM exercise with ten repetitions.Results and Discussion: Independent Sample T-Test shows significant difference in HIT scale. P value is 0.046. It shows no significant difference in DHI scale. P value is 0.235.Conclusion: In this study exercise protocol is effective for headache and migraine related disability in VM patients. Exercise protocol is not effective to reducing vestibular symptoms in VM patients.